2008
DOI: 10.1111/j.1600-0854.2008.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Arf3p Modulates Plasma Membrane PtdIns(4,5)P2 Levels to Facilitate Endocytosis

Abstract: Phosphatidylinositol-(4,5)-bisphosphate [PtdIns(4,5)P2] is a key regulator of endocytosis. PtdIns(4,5)P2 generation at the plasma membrane in yeast is mediated by the kinase Mss4p, but the mechanism underlying the temporal and spatial activation of Mss4p to increase formation of PtdIns(4,5)P2 at appropriate sites is not known. Here, we show that ADP ribosylation factor (Arf)3p, the yeast homologue of mammalian Arf6, is necessary for wildtype levels of PtdIns(4,5)P2 at the plasma membrane. Arf3p localizes to dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…Similarly, Arf6 stimulates recruitment and activation of type I PIP5 kinases at the plasma membrane and endosomes [6,7], a property shared with its yeast counterpart, yArf3 [8]. At both the Golgi and the plasma membrane, the Arf-dependent recruitment of PtdIns kinases results in enhanced local production of PtdIns(4,5)P 2 .…”
Section: Arfs Phosphoinositides and The Cytoskeletonmentioning
confidence: 98%
“…Similarly, Arf6 stimulates recruitment and activation of type I PIP5 kinases at the plasma membrane and endosomes [6,7], a property shared with its yeast counterpart, yArf3 [8]. At both the Golgi and the plasma membrane, the Arf-dependent recruitment of PtdIns kinases results in enhanced local production of PtdIns(4,5)P 2 .…”
Section: Arfs Phosphoinositides and The Cytoskeletonmentioning
confidence: 98%
“…These various data clearly link Arf3 with the endocytic machinery. Analysis of plasma membrane PtdIns(4,5)P2 levels indicate that Arf3 can serve to increase production of this lipid, presumably via the only phosphatidylinositol 4 phosphate 5 kinase in yeast, Mss4 [81]. The production of PtdIns(4,5)P2 is known to be critical for endocytosis as a site for binding the ANTH domain protein Sla2 [32].…”
Section: Lipids and The Regulation Of Actin In Endocytosismentioning
confidence: 98%
“…More recently, interactions have also been shown with ArfGEF and ArfGAP proteins. Of these, its guanine exchange factor (GEF) localizes to the plasma membrane in an Arf3-dependent manner [80,81]. The ArfGAP, Gts1 shows extensive overlap in its localization with the endocytic machinery and interacts with many components, including Sla1, Pan1, YAP1801/2 and the clathrin light chain.…”
Section: Lipids and The Regulation Of Actin In Endocytosismentioning
confidence: 99%
“…Similarly, the ARF-GAP VASCU-LAR NETWORK DEFECTIVE 3 (VAN3) controls auxin transport-mediated processes such as vascular tissue formation (9,10), and its cellular role, although not entirely clear, has been mapped to the endosomal compartments (9,11). In contrast to the extensive data in yeast and mammals (4,12,13), very little is known about the direct involvement of the ARF machinery in the endocytosis of plants (14)(15)(16). It has been suggested that the GNOM-like 1 (GNL1) ARF-GEF, the closest homolog of GNOM, regulates the internalization of the PIN2 auxin transporter (17), but its action remained unclear because the loss-offunction gnl1 mutants did not show any endocytosis defects per se (18).…”
mentioning
confidence: 99%